Expression de l’exclamation en anglais au moyen de marqueurs atypiques - Bénédicte Guillaume; Emmanuel Baumer (Corela)
In this paper we will discuss the exclamative values of some question tags and of the quantifier some, within the framework of A. Culioli’s Theory of Enunciative Operations. Although these markers are not typical of the expression of exclamation, we aim at showing that they are compatible with an exclamative value, because they present certain semantic, syntactic and prosodic features which are also found in exclamatory sentences. Our study is based on a corpus of attested examples of British or American English sampled from various sources (namely, the British National Corpus as well as novels and TV series), both in their written and in their oral forms. The main conclusion to be drawn from the analysis of the context of the examples is that the exclamative interpretation which can be felt is linked to a strong disagreement between the speakers. It is therefore a high degree (which is a technical term in Culioli’s framework) of controversy which tends to generate the exclamative interpretation of such phrases, which are not, otherwise, typical of exclamatory sentences. At the level of intonation, the recourse to the Praat software helps to evidence such phenomena as pitch variation or vowel lengthening, which for their part are essential as far as an exclamative interpretation is concerned.